1997
DOI: 10.1007/s11738-997-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium effect on hydrogen peroxide, gluthatione and phytochelatins levels in potato tuber

Abstract: Key words." C a d m i u m , Gh_tthatione, H y d r o g e n peroxide, O x i d a t i v e stress, Phytochclatins, SoZJ, m.m~ mbero,vwn L. AbstractShort-tcm~ treatment of potato tuber (Solcmum tuber(~sum L.} discs wi@ CdC12 (imM) induced all oxidative stress, manifested by higher levels o{I I:-O,, and aclivated the sym'hesi~ of phytochclath~s ((;/--G hL Cys)n-Gly): PC2, 1<'.3 and PCa. l fin the tissues with a bwer GSH level, the oxidative slress was induccd by h-eminent with 3 amhmtriazo] (AT), or with AT arid H:~O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…This is most likely due to metal-induced disturbance of AOS-generating metabolism and deactivation of the processes required for AOS destruction (Dietz et al, 1999). Accumulation of hydrogen peroxide (H 2 O 2 ) is a typical response of many plant species to toxic concentrations of Cd (Romero-Puertas et al, 1999;Schützendübel et al, 2001;Stroinski and Zielezinska, 1997). Cd has been found to trigger oxidative burst in tobacco cells within minutes of exposure (Piqueras et al, 1999), possibly signaling the first defenses against heavy metals at the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…This is most likely due to metal-induced disturbance of AOS-generating metabolism and deactivation of the processes required for AOS destruction (Dietz et al, 1999). Accumulation of hydrogen peroxide (H 2 O 2 ) is a typical response of many plant species to toxic concentrations of Cd (Romero-Puertas et al, 1999;Schützendübel et al, 2001;Stroinski and Zielezinska, 1997). Cd has been found to trigger oxidative burst in tobacco cells within minutes of exposure (Piqueras et al, 1999), possibly signaling the first defenses against heavy metals at the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…PCs contribute to Cd tolerance in many plants (Steffens et al 1986;Gupta and Goldsbrough 1991;Stroinski and Zielezinska 1997). In the CW and CCdl cells, the PC synthesis was enhanced under Cd exposure (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, another mechanism of Cd detoxification is present in the CCdl cells. According to some reports, Cd induces the activity of a catalase (Stroinski and Koz10wska 1997;Stroinski and Zielezinska 1997) and guaiacol and ascorbate peroxidases (Reddy and Prasad 1992;Chaoui et al 1997) in plants. We have recently observed that the antioxidative defense system is also enhanced by Cd in carrot cells.…”
Section: Discussionmentioning
confidence: 99%
“…PCs were isolated and separated according to Stroiński & Zielezińska (1997), using the method presented by Tukendorf & Rauser (1990). Frozen leaves (0.5 g) were homogenized with an Art-Miccra homogenizer in 2 ml of 0.5 mmol dm -3 HCl.…”
Section: Thiols Content and Phytochelatin Synthase Activitymentioning
confidence: 99%